The efficiency of copper ore comminution: A thermodynamic exergy analysis. (1st August 2017) - Jacob, Wilhelm; Cooper, Daniel R.; Gutowski, Timothy; Ramos-Grez, Jorge
Highlights: Implementation of a minimum comminution work index based on the uniaxial compression testing of mineral ore. Obtain a Hukki-Morrell fitted relationship and determine comminution work of a laboratory sized dry ball mill. Compare limitations when using the Hukki-Morrell fitted model against an inertial energy estimation. Perform an exergy analysis for comminution work in a laboratory sized dry ball mill. Abstract: This study analyzes the exergy efficiency of comminution using a laboratory sized dry ball mill and a copper mineral ore from central Chile. In this research, we develop a minimum work index from uniaxial compression tests results on the ore fitted to Morrell's comminution energy equation using Hukki's constant mineral parameter. An exergy analysis is then performed on a laboratory sized dry ball mill by considering the surface energy variation for different ore sizes, the obtained Hukki-Morrell fitted relationship from the compression tests of the ore and the minimum inertial energy required during a dry-ball milling process. The theoretical minimum work needed to crush the rock is first calculated by comparing the difference in surface energy between the incoming ore and the outgoing crushed rock. However, this analysis (based on the creation of new surfaces) suggests an impractical low minimum work of little use as a benchmark. Instead, use of the Hukki-Morrell relationship evaluated at the resulting ore particle sizes suggests a practical benchmark. Using this benchmark for the laboratory's dry ball mill process renders an efficiency of approximately 3%. One could use the heat from the outgoing crushed ore to, theoretically perform work, but the heat flows through at a low temperature that this change would only increase the efficiency to 3.1%. We also consider the inertial energy needed to drive the ball mill employing it as a new benchmark for our efficiency calculation. The latter raises the efficiency of the dry ball milling to an average 23%. Finally, electrical energy measurements and inertial calculations on operating an empty versus loaded ball mill suggest that the efficiency could be increased by ensuring correct machinery scaling (diameter of the drum shell), ball load and a properly maintained transmission system.